Social-Emotional Competences of Preschoolers: The Impact of Outdoor Educational Activities - Clipa, Otilia (Erziehungskonzeptionen und Praxis, 2020)
Early childhood education is a new & priority of European trends education and a means of increasing the quality of the life. This study aims to provide an analysis of the kindergartens in nature experiences, where children's lives are conducted in close contact with nature and the outdoor activities in any season and in any weather are an important part of the daily program. These outdoor activities have a significant contribution to social and emotional development of the preschoolers. The concept of kindergartens in nature is an innovative educational concept in which the education for sustainable management and environment has an integrated approach. These activities contribute to the social and emotional development of preschoolers.